Impact of Sarcopenia on the Severity of the Liver Damage in Patients With Non-alcoholic Fatty Liver Disease - Zambon Azevedo, Vittoria; Silaghi, Cristina Alina; Maurel, Thomas; Silaghi, Horatiu; Ratziu, Vlad; Pais, Raluca (Frontiers in Nutrition, 2022)
An extensive body of the literature shows a strong interrelationship between the pathogenic pathways of non-alcoholic fatty liver disease (NAFLD) and sarcopenia through the muscle-liver-adipose tissue axis. NAFLD is one of the leading causes of chronic liver diseases (CLD) affecting more than one-quarter of the general population worldwide. The disease severity spectrum ranges from simple steatosis to non-alcoholic steatohepatitis (NASH), cirrhosis, and its complications: end-stage chronic liver disease and hepatocellular carcinoma. Sarcopenia, defined as a progressive loss of the skeletal muscle mass, reduces physical performances, is associated with metabolic dysfunction and, possibly, has a causative role in NAFLD pathogenesis. Muscle mass is a key determinant of the whole-body insulin-mediated glucose metabolism and impacts fatty liver oxidation and energy homeostasis. These mechanisms drive the accumulation of ectopic fat both in the liver (steatosis, fatty liver) and in the muscle (myosteatosis). Myosteatosis rather than the muscle mass per se, seems to be closely associated with the severity of the liver injury. Sarcopenic obesity is a recently described entity which associates both sarcopenia and obesity and may trigger worse clinical outcomes including hepatic fibrosis progression and musculoskeletal disabilities. Furthermore, the muscle-liver-adipose tissue axis has a pivotal role in changes of the body composition, resulting in a distinct clinical phenotype that enables the identification of the “sarcopenic NAFLD phenotype”. This review aims to bring some light into the complex relationship between sarcopenia and NAFLD and critically discuss the key mechanisms linking NAFLD to sarcopenia, as well as some of the clinical consequences associated with the coexistence of these two entities: the impact of body composition phenotypes on muscle morphology, the concept of sarcopenic obesity, the relationship between sarcopenia and the severity of the liver damage and finally, the future directions and the existing gaps in the knowledge.